The effect of mental fatigue on half-marathon performance: a pragmatic trial - Gattoni, C.; O`Neill, B. V.; Tarperi, C.; Schena, F.; Marcora, S. M. (Sport Sciences for Health, 2021)
Purpose: It is well established that mental fatigue impairs performance during lab-based endurance tests lasting less than 45 min. However, the effects of mental fatigue on longer duration endurance events and in field settings are unknown. The aim of this study was to investigate the effect of mental fatigue on performance during a half-marathon race. Methods: Forty-six male amateur runners (means ± SD: age 43.8 ± 8.6 years, VO2peak 46.0 ± 4.1 ml/kg/min) completed a half-marathon after being randomly allocated to performing a 50-min mentally fatiguing task (mental fatigue group) or reading magazines for 50 min (control group). Running speed, heart rate, and perceived effort were measured during the race. Results: Runners in the mental fatigue group completed the half-marathon approximately 4 min slower (106.2 ± 12.4 min) than those in the control group (102.4 ± 10.2 min), but this difference was not statistically significant (Cohen`s d = 0.333; p = 0.265). However, equivalence was not established [t(40.88) = 0.239, p = 0.594] and equivalence testing analysis excluded a beneficial effect of mental fatigue on half-marathon performance. Conclusion: Due to its posttest-only design and the achievable sample size, the study did not have enough power to provide evidence that the observed 4-min increase in half-marathon time is statistically significant. However, equivalence testing suggests that mental fatigue has no beneficial effect on half-marathon performance in male amateur runners, and a harmful effect cannot be excluded. Overall, it seems prudent for endurance athletes to avoid mentally fatiguing tasks before competitions.